2023
DOI: 10.5194/egusphere-egu23-10599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric observation and source analysis of CFCs, HCFCs and HFCs at the Medog background site on the southern slope of the Himalayas, China

Abstract: <p>The ozone-depleting substances chlorofluorocarbons (CFCs), hydrochlorofluorocarbons (HCFCs) and their major substitutes hydrofluorocarbons (HFCs) are all potent greenhouse gases, and their atmospheric concentrations and emission sources have received international attention. The relevant studies have been carried out at multiple background sites around the world, but there is no report on the southern slope of the Himalayas. For the first time, this study set up the Medog backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[55] A higher printing temperature produced greater bond performance and thus better mechanical performance because it enabled greater molecular chain diffusion and entanglement across the bond interface. [53,56] By contrast, the melt viscosity of the BF/L-PA composites increased, and the flowability decreased under lower printing temperatures. Under these conditions, poor interlayer cohesion resulted in reduced mechanical properties.…”
Section: Effects Of Printing Temperature On Tensile and Compression P...mentioning
confidence: 99%
See 1 more Smart Citation
“…[55] A higher printing temperature produced greater bond performance and thus better mechanical performance because it enabled greater molecular chain diffusion and entanglement across the bond interface. [53,56] By contrast, the melt viscosity of the BF/L-PA composites increased, and the flowability decreased under lower printing temperatures. Under these conditions, poor interlayer cohesion resulted in reduced mechanical properties.…”
Section: Effects Of Printing Temperature On Tensile and Compression P...mentioning
confidence: 99%
“…When the melt temperature reached 195 C, the MFR of the BF/L-PA significantly increased, which was $35% higher than that at 185 C. This was because the high temperature could release the condensation and entanglement between molecular chains to increase molten flowability. [53] The printing temperature of 225 C was selected for the FDM printing test to study the feasibility of the 3D printing of BF/L-PA composites. It was observed that the flow velocity of composites at 225 C was so high that nozzle leakage occurred.…”
Section: Mfr Of 3d-printed Compositesmentioning
confidence: 99%